Gas sensing based on detection of light radiation from a region of modified cladding (nanocrystalline ZnO) of an optical fiber. (March 2017) - Devendiran, S.; Sastikumar, D.
Abstract: A new type of fiber optic gas sensor is proposed by detecting a light radiated from a region of cladding modified with metal oxide (nanocrystalline ZnO). The intensity of radiated light is found to vary with different gasses and concentrations. Sensing characteristics are studied for ammonia, methanol, ethanol and acetone gasses. Gas sensitivity of the proposed sensor is compared with clad-modified fiber optic gas sensor. The new sensor exhibits enhanced sensitivity. Time response characteristics of the sensor are reported. Highlights: New type of fiber optic gas sensor is proposed The sensor can be operated at room temperature The sensitivity of the new type of sensor is higher (3–6 times) than the clad-modified fiber optic sensor